2013
DOI: 10.1063/1.4808376
|View full text |Cite|
|
Sign up to set email alerts
|

The electrostatic response of water to neutral polar solutes: Implications for continuum solvent modeling

Abstract: Continuum solvation models are widely used to estimate the hydration free energies of small molecules and proteins, in applications ranging from drug design to protein engineering, and most such models are based on the approximation of a linear dielectric response by the solvent. We used explicit-water molecular dynamics simulations with the TIP3P water model to probe this linear response approximation in the case of neutral polar molecules, using miniature cucurbituril and cyclodextrin receptors and protein s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 86 publications
0
17
0
Order By: Relevance
“…Previous studies have shown that explicit water effects might play an important role in binding for the CB7 system [20, 21, 47, 48], and suggested that expulsion of thermodynamically disfavored structured waters in the host’s cavity might drive the high binding affinities of some guests for CB7. Nonetheless, the overall performance has been similar for both continuum and explicit-water solvation models, and some of the better performing methods here used continuum solvation models.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that explicit water effects might play an important role in binding for the CB7 system [20, 21, 47, 48], and suggested that expulsion of thermodynamically disfavored structured waters in the host’s cavity might drive the high binding affinities of some guests for CB7. Nonetheless, the overall performance has been similar for both continuum and explicit-water solvation models, and some of the better performing methods here used continuum solvation models.…”
Section: Discussionmentioning
confidence: 99%
“…Hydration free energies were computed through stepwise decoupling of the solute from the solvent [42]. The decoupling was carried out in two main stages: first, the electrostatic interactions between solute and water were decoupled in 10 steps with coupling parameter values of λ = [0.00, 0.10, 0.20, 0.30, 0.40, 0.50, 0.60, 0.70, 0.80, 0.90, 1.00].…”
Section: Methodsmentioning
confidence: 99%
“…A hierarchy of approximations, many of which are essentially unavoidable, separates the PB (and the GB) from the more fundamental explicit solvent representation, and from reality . These approximations result in notable limitations of the pure GB or PB frameworks, such as their inability to account for many prominent explicit solvent effects, including charge hydration asymmetry and other water multipole effects, water ‘bridges,’ electrostriction and dielectric saturation . Also, accurate estimates of total solvation energies, and especially their differences in conformational transitions, need accurate nonpolar estimates of the nonpolar contribution .…”
Section: Implicit Solvent Modelsmentioning
confidence: 99%